Usage of the Floor-Lifting Method for Buildings Erection with Precast-Monolithic Reinforced Concrete Frames of «KUB» or Similar Frame Systems - Dyachenko, Evgen; Zyma, Oleksandr; Scherbinin, Leonid; akarenko, Ruslan M (International Journal of Engineering and Technology, 2018)
Usage of the floor-lifting method for buildings erection with precast-monolithic reinforced concrete frames of «KUB» or similar frame system was reviewed in the article. Analysis of technological features of proposed method was done. Advantages and disadvantages of proposed method usage were listed. Opportunity of floor-lifting method of reinforced concrete frames buildings erection in dense areas usage was justified. Usage of the floor-lifting method for erection of buildings with precast-monolithic reinforced concrete frames of «KUB» or similar frame system allows to reduce the works complexity due to the complete refusal to use the equipment for the verification and temporary fixing of slabs individual elements and the operations exclusion associated with the retrieval and temporary fixing floor slabs elements. Proposed method usage allows to move majority of assembly operations to the ground floor level, which can significantly increase the industrial safety level, improve the work and control quality. Reducing the installation parameters values, allows to use less powerful self-propelled cranes for building frame elements installation, in some cases, completely refuse to use the tower cranes. It makes sense to use this building frameworks erection method in dense urban areas. The main disadvantage of this method is the high demanding quality of the slabs elements production. Because the surface of the slab is the basis for the next floor slab, inaccurate factory production will not allow the exact slabs elements installation in the required position.